A influência do polimorfismo do superóxido dismutase dependente de manganês 2 na morbi-mortalidade pós-operatória de pacientes submetidos a cirurgias oncológicas - Piantá, Christina Duarte (2005)
Cancer is one of the leading causes of morbidity and mortality in Brazil and worldwide, and surgery is very often its primary treatment. Manganese-dependent superoxide dismutase (SOD 2) is one of the main intracellular antioxidant enzymes, participating directly in the protection of the cell against oxidative reactions, which are thought to be pivotal in carcinogenesis. Diminished expression of SOD 2 is found in a number of different neoplasms, and in some of them is correlated to an adverse prognosis. The present study was designed to correlate SOD 2 genetic polymorphism with postoperative morbidity and mortality in patients submitted to oncologic surgery at a university hospital, and to characterize the postoperative complications observed. We performed a prospective, observational study of 88 adult patients submitted to oncologic surgeries. Mean + SD age was 61 + 7.4 years; 59% of patients were male. Some co-morbidity was present in 76% of patients in the preoperative evaluation, of which the most common was arterial hypertension (47.7%). Most surgeries were performed in the gastrointestinal tract (85.2%), in most cases approaching the stomach or colon. Adenocarcinoma of the gastrointestinal tract was the most commonly found histological tumor type (80.7%). In 30.7 of patients, there was lymph node involvement. Postoperative complications occurred in 57% of patients, with sepsis (27.3%) and bronchopneumonia (11.4%) being the most frequent. Operative mortality (up to 30 postoperative days) was of 21.6%; the main cause of death was sepsis (63.2%). Allelic frequencies of SOD 2 genetic polymorphisms were: allele A 54% and allele B 45%. Genotypic frequencies observed were: genotype AA 34.1%, genotype BB 25%, and genotype AB 40.9%. There was no statistically significant association between preoperative variables and SOD 2 genetic polymorphism. The only postoperative variable associated to SOD 2 genetic polymorphism was urinary tract infection, which occurred exclusively in AA genotype patients (P = 0.002). When we evaluated the association between the presence of the A allele (genotypes AA and AB) of SOD 2 and preoperative variables, there was a positive correlation with diabetes mellitus (P = 0.04). There was no association between the presence of the A allele (genotypes AA and AB) and postoperative variables. When we evaluated the association of the presence of the B allele (genotypes AB and BB) of SOD 2 and preoperative variables, there was a positive correlation with cardiovascular disease (P = 0.01). When we evaluated the association of the presence of the B allele (genotypes AB and BB) of SOD 2 and postoperative variables, there was a positive correlation with urinary tract infections (P = 0.001) and stroke (P = 0.04). There was a borderline association between the presence of the B allele (genotypes AB and BB) of SOD 2 enterocutaneous fistula (P = 0.1). The present study implies that SOD 2 gene polymorphism does not seem to significantly influence postoperative morbidity and mortality in patients submitted to oncologic surgery.